Morphological and physiological plasticity of plant roots when nutrients are both spatially and temporally heterogeneous - Mou Pu; Bao Zhe; Chen Hongmei; Jones HRobert; Tan Zengquan (Plant and Soil, 2013)
Background and aims: Roots express morphological and physiological plasticity that may be adaptations for effecient nutrient capture when soil nutrients are heterogeneous in space and time. In terms of nutrient capture per unit of carbon invested in root, morphological plasticity should be more advantageous when nutrient patches are stable in time, and physiological plasticity when nutrients are variable in time. Methods: Here we examined both traits in two pinus species, Ailanthus altissima and Callistephus chinesis, grown in pots where the same total level of nutrient addition was provided in a factorial experiment with different levels of spatial and temporal variability. Results: Total plant root growth, root/Shoot ratios and morphological plasticity were less when nutrients were temporally variable instead of stable. Physiological plasticity was more variable than morphological across treatments and species and was not predictably greater when nutrient supply was pulsed instead of constant. Large variability, especially in physiological plasticity, was observed, and physiological plasticity was greater in non-woody than on woody species. Conclusions: Our results suggests that the two traits differ in environmental factors that control their expression, and that the nature of nutrient patchiness may have more direct impact on the evolution of morphological than physiological plasticity.
Keywords: Morphological plasticity; Physiological plasticity; Root nutrient foraging; Root/shoot ratio; Soil nutrient heterogeneity